Implementation of Black Box Testing and System Usability Scale on the Nurul Huda Financial Recording Information System - Ramadan, Mohammad Noval; Ramadhani, Muhammad Azka Robith; Handayani, Chika Tunas; Sulistiyani, Endang; Budiarti, Rizqi Putri Nourma (TEKNOLOGI DITERAPKAN DAN JURNAL SAINS KOMPUTER, 2024)
This study was conducted to evaluate the performance of the Nurul Huda Foundation’s financial recording information system using two assessment methods: Black Box Testing and usability measurement through the System Usability Scale (SUS). Black Box Testing was applied to ensure that all system features operate as intended, while usability testing was carried out to determine the level of comfort and ease experienced by users when interacting with the system. The results of the Black Box Testing indicate that out of 111 test scenarios, 89 passed successfully and 22 experienced minor failures that remain within acceptable improvement limits. Meanwhile, the usability testing involving 20 respondents produced an average SUS score of 84.5, demonstrating that the system meets the criteria of being user-friendly and positively received by users. Based on SUS interpretation guidelines by Bangor, this score falls into Grade A with an “Excellent” rating, is categorized as “Acceptable,” and is classified under the Net Promoter Score (NPS) group of “Promoter”.